Depression storage and infiltration effects on overland flow depth-velocity-friction at desert conditions: Field plot results and model - Rossi, María Julieta (2012)
Water infiltration and overland flow are relevant in considering water partition among plant life forms, the sustainability of vegetation and the design of sustainable hydrological models and management. In arid and semi-arid regions, these processes present characteristic trends imposed by the prevailing physical conditions of the upper soil as evolved under water-limited climate. A set of plot-scale field experiments at the semi-arid Patagonian Monte (Argentina) were performed in order to estimate the effect of depression storage areas and infiltration rates on depths, velocities and friction of overland flows. The micro-relief of undisturbed field plots was characterized at z-scale 1 mm through close-range stereo-photogrammetry and geo-statistical tools. The overland flow areas produced by controlled water inflows were video-recorded and the flow velocities were measured with image processing software. Antecedent and post-inflow moisture were measured, and texture, bulk density and physical properties of the upper soil were estimated based on soil core analyses. Field data were used to calibrate a physically-based, mass balanced, time explicit model of infiltration and overland flows. Modelling results reproduced the time series of observed flow areas, velocities and infiltration depths. Estimates of hydrodynamic parameters of overland flow (Reynolds-Froude numbers) are informed. To our knowledge, the study here presented is novel in combining several aspects that previous studies do not address simultaneously: (1) overland flow and infiltration parameters were obtained in undisturbed field conditions; (2) field measurements of overland flow movement were coupled to a detailed analysis of soil microtopography at 1 mm depth scale; (3) the effect of depression storage areas in infiltration rates and depth-velocity friction of overland flows is addressed. Relevance of the results to other similar desert areas is justified by the accompanying biogeography analysis of similarity of the environment where this study was performed with other desert areas of the world.